Desenvolvimento e implementação de modelos de cálculo para análise térmica microclimática em ambiente SIG - Favretto, Ana Paula Oliveira (Universidade Federal de São Carlos, 2021)
The urbanization impact over the microclimate highlights the importance of using climatological criteria to guide urban planning. The advent and development of Geographic Information System (GIS) plays an important role in climate guided urban planning breakthroughs, as it allows data layering and predictive analyses. A calculation model to automate the Frontal Area Index (FAI) and Thermal Potential Index (TPI) mapping, and the prediction of wind and cooling routes based on Least Cost Path analyses over the generated maps is developed and implemented in this research. The calculation model is implemented as a group of Python Script Tools embedded in ESRI© ArcGIS Pro 2.7.0. For that we used the ArcPy Python Library, which allows to access ArcGIS geoprocessing functions. A detailed description of the calculation model is presented and can be used to implement tools in other GIS platforms. The generated Script Tools are easy to use and its results allow the urban morphology assessment and also the study of its influence over wind route patterns. In this way, this research contributes both to advance of the Urban Climatology scientific field and to guide urban planner’s practical decision making.
Development and implementation of calculation models for microclimate thermal analysis in a GIS environment
Keywords: Conforto ambiental; Conforto térmico urbano; Ilha de calor urbana; Índice de área frontal; Planejamento urbano; Ventilação urbana; Superfície de cobertura do solo; Modelo simplificado; SIG; Environmental comfort; Urban thermal comfort; Urban heat island; Urban planning; Frontal area index; Urban ventilation; Ground cover; Simplified model; GIS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL